PENINGKATAN KOMPETENSI GURU BAHASA INGGRIS SMP DI KABUPATEN BOGOR MELALUI PELATIHAN PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS ANIMAKER - sylvia, sylvia; Bachtiar, Bachtiar; Zuhairi, Aminuddin; Puspitasari, Maya; Gardina, Inggit (Jurnal Abdi Insani, 2026)
In the era of digital transformation, teachers are expected to integrate technology into classroom practices to enhance students’ engagement and 21st-century skills. Within the framework of the Merdeka Belajar curriculum, technology-enhanced learning plays a vital role in fostering creativity, collaboration, communication, critical thinking, and character development. However, many English teachers still face challenges in utilizing digital tools effectively due to limited technological competence and pedagogical readiness. This community service (Pengabdian kepada Masyarakat or PkM) program was designed to strengthen the digital and pedagogical capacities of junior high school English teachers in Bogor Regency through training on the development of deep learning–based instructional videos using the Animaker platform. The activity was conducted on September 26, 2025, and involved 36 teachers who are members of the Musyawarah Guru Mata Pelajaran (MGMP) English Teachers Association. The program adopted a four-stage model consisting of observation, socialization, training and mentoring, and evaluation. Data were collected through observation, participant feedback, and reflective discussions. The findings indicate that the program significantly improved teachers’ understanding and skills in designing and producing animation-based instructional videos. Teachers demonstrated greater creativity, confidence, and motivation in integrating technology into their English lessons. Moreover, the training fostered collaborative learning, reflective practice, and professional growth among participants. This program highlights the importance of ongoing professional development and institutional support in equipping teachers with digital pedagogical competencies to meet the demands of modern education.